Scale microornamentation of five species of Pareas (Serpentes, Pareidae) from China - Guo, Yuhong; Wang, Guangli; Rao, Dingqi (Zootaxa, 2020)
Due to the highly conserved morphology of its members, the taxonomy of Pareas remains contentious. Microornamentation was examined on the exposed surfaces of dorsal scales from the midbody region of five species of genus Pareas. The results showed that the ultrastructural characteristics are similar in some respects and different in others. Similarly, all species exhibit arc and pore structures, but the shape, number and arrangement of these arcs and pores differ. In particular, the microornamentation of the dorsal scales of Pareas yunnanensis, thus far regarded as a synonym of P. chinensis, is obviously different from that of P. chinensis. Thus, P. yunnanensis is revalidated. The ultrastructural characteristics of these five species of Pareas are very different from those of reported for P. carinatus. P. carinatus may not belong to the same genus as other Pareas species.